Anti-wear characteristics of jatropha trimethylolpropane (TMP) ester - Mohd Zulkifli, Nurin Wahidah; Kalam, Md. Abul; Yunus, Robiah; Hassan, Masjuki (Malaysian Tribology Society, 2011)
This paper presents the experimental results from an evaluation of the wear prevention characteristics of a jatropha oil-based trimethylolpropane (TMP) ester using a four-ball machine (ASTM D4172). The load, speed and lubricant sample temperature were set at 40 kgf (393 N), 1200 rpm and 75 °C, respectively. Under these test conditions, the wear and friction characteristics of different TMP samples were measured and compared. The TMP ester was produced from jatropha; it is biodegradable and has high lubricity properties such as a higher flash point temperature and viscosity index (VI). It has an affinity to surface at asperity, hence reduces wear between sliding contacts. The results presented in this investigation include the viscosity index (VI), density, total acid number (TAN), total base number (TBN), wear scar diameter (WSD), coefficient of friction (COF), a wear micrograph using scanning electron microscopy (SEM) and the surface roughness of ball wear. It was found that at certain blends of TMP in the lubricant decreased WSD and COF. Sample TMP10 (10% TMP and 90% original lubricant) showed the lowest wear and COF, as confirmed by SEM results. The results of this investigation will be used to develop new and efficient lubricants for automotive engines.